High-entropy amorphous NiCoFeOS and low-crystallization CeO2 heterojunction electrocatalyst as well as preparation method and application thereof
By constructing a heterojunction structure of high-entropy amorphous NiCoFeOS and low-crystalline CeO2, the problems of few active sites and weak chlorine corrosion resistance of transition metal sulfides are solved, and efficient electrolytic catalysts are achieved, which improves the efficiency of hydrogen production and stability.
Patent Information
- Application Number
- CN202411360364.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
Transition metal sulfides have few active sites, low intrinsic activity and weak chlorine corrosion resistance in water/seawater electrolysis, which limits their application in large-scale hydrogen production.
High-entropy amorphous NiCoFeOS and low-crystalline CeO2 heterojunction catalyst are used to form a high-entropy amorphous-low-crystalline heterostructure through electrodeposition, increasing active sites and electronic communication, and improving catalytic activity and corrosion resistance.
The catalytic activity and stability of the electrocatalyst is significantly improved, the electrolytic performance is enhanced, the preparation process is simplified, the cost is reduced, and efficient hydrogen production is achieved.
Smart Images

Figure CN119243235A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy materials and electrochemical catalysis, and specifically relates to a high-entropy amorphous NiCoFeOS and low-crystalline CeO2 heterojunction electrocatalyst, and a preparation method and application thereof. Background Art
[0002] Hydrogen energy is one of the best solutions to the energy crisis and environmental pollution. High energy density, wide availability, and green H2O products make hydrogen a promising renewable candidate for fossil fuels. Therefore, large-scale hydrogen production will contribute to the green energy transition. Water / seawater electrolysis is one of the effective technologies for large-scale production of green hydrogen due to its simple process, low equipment requirements, and abundant reserves. The entire water / seawater electrolysis process consists of two half reactions, namely the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. The efficiency of water / seawater electrolysis determines the production of hydrogen, which depends on the activity and stability of the HER / OER electrocatalyst.
[0003] Transition metal sulfides, especially nickel-cobalt sulfides, have attracted much attention due to their excellent electrochemical performance, ease of preparation, and abundant reserves in HER / OER. However, the few active sites, low intrinsic activity, and weak chlorine corrosion resistance of single-phase sulfides have become the bottleneck for their widespread application in water / seawater electrolysis. Summary of the invention
[0004] To solve the above problems, the present invention provides a high-entropy amorphous NiCoFeOS and low-crystalline CeO2 heterojunction (NiCoFeOS / CeO2) electrocatalyst and a preparation method and application thereof.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention is to provide a method for preparing a high entropy amorphous NiCoFeOS and low crystalline CeO2 heterojunction electrocatalyst, comprising the following steps:
[0007] Dissolving a soluble nickel salt, a soluble cobalt salt, a soluble iron salt, a soluble cerium salt, thiourea and ammonium sulfate in water to prepare an electrodeposition solution;
[0008] The electrodeposition liquid is used to form an electrodeposition layer on a substrate through electrodeposition, and the electrodeposition layer is the high-entropy amorphous NiCoFeOS and low-crystalline CeO2 heterojunction electrocatalyst.
[0009] The present invention solves the defects of transition metal sulfides such as few active sites, low inherent activity, and weak chlorine corrosion resistance through a modification strategy combining heterogeneous structure, vacancies, high entropy and phase structure.
[0010] First, the high entropy amorphous structure in the electrocatalyst constructed by the present invention can increase the active sites of unsaturated structures with long-range disorder but medium- and short-range ordered structures, which is a promising strategy for fine electronic structure modulation and easy-to-control synthesis, facilitating the rational design of efficient oxysulfide electrocatalysts. The high entropy strategy composed of multiple components (≥5) effectively regulates the d-band center and promotes reaction kinetics. Amorphous transition metal oxysulfide-based electrocatalysts with more active sites show higher activity than crystalline catalysts.
[0011] Secondly, due to the good electronic communication between different components, the high-entropy amorphous structure and low-crystalline heterojunction structure in the constructed electrocatalyst are also very promising regulation strategies for efficient bifunctional catalysts for water electrolysis.
[0012] In addition, the electrodeposition layer strategy provided by the present invention is suitable for the preparation of multi-component mixed metals, and can realize the preparation of high-performance multi-component electrocatalysts, and the method is simple and efficient.
[0013] Preferably, the molar ratio of nickel in the soluble nickel salt, cobalt in the soluble cobalt salt, iron in the soluble iron salt and cerium in the soluble cerium salt is 0.9-1.1:0.9-1.1:0.9-1.1:0.9-1.1
[0014] More preferably, the molar ratio of nickel in the soluble nickel salt, cobalt in the soluble cobalt salt, iron in the soluble iron salt and cerium in the soluble cerium salt is 1:1:1:1.
[0015] Preferably, the molar ratio of the total amount of metal sources in the soluble nickel salt, the soluble cobalt salt, the soluble iron salt and the soluble cerium salt to the thiourea is 1:2.8-3.2.
[0016] More preferably, the molar ratio of the total amount of metal sources in the soluble nickel salt, the soluble cobalt salt, the soluble iron salt and the soluble cerium salt to the thiourea is 1:3.
[0017] Preferably, the soluble nickel salt is nickel sulfate; the soluble cobalt salt is cobalt sulfate; the soluble iron salt is ferrous sulfate; and the soluble cerium salt is cerium nitrate.
[0018] The role of ammonium sulfate in electrodeposition is to promote the redox reaction during the electrodeposition process and improve the quality and stability of the electrodeposited layer. Ammonium sulfate can be added according to the conventional usage amount.
[0019] Preferably, the electrodeposition is intermittent electrodeposition.
[0020] More preferably, the deposition voltage of the intermittent electrodeposition is -1.8 V, the static voltage is 0, each voltage holding time is 10 s, and the total intermittent electrodeposition time is 2400 s.
[0021] Preferably, the substrate is nickel foam (NF); in the electrodeposition, the working electrode is nickel foam, the counter electrode is a carbon rod, and the reference electrode is Ag / AgCl.
[0022] The second technical solution of the present invention is to provide a high-entropy amorphous NiCoFeOS and low-crystalline CeO2 heterojunction electrocatalyst prepared according to the above preparation method.
[0023] The third technical solution of the present invention is to provide an application of the above-mentioned high-entropy amorphous NiCoFeOS and low-crystalline CeO2 heterojunction electrocatalyst in water electrolysis.
[0024] The beneficial technical effects of the present invention are as follows:
[0025] The present invention provides a method for preparing a high-entropy amorphous NiCoFeOS and low-crystalline CeO2 heterojunction electrocatalyst. The prepared NiCoFeOS / CeO2 electrocatalyst is a nanosphere structure uniformly loaded on a substrate. The excellent catalytic performance of the NiCoFeOS / CeO2 electrocatalyst is attributed to the following aspects: 1) The catalyst is prepared by electrodeposition on a substrate in one step to obtain a high-entropy amorphous-low-crystalline heterojunction catalyst, which has the advantages of being simple, rapid, efficient and low-cost; 2) The high-entropy amorphous-low-crystalline heterostructure has abundant defects and active sites, and enhanced charge transfer occurs at the active interface between the amorphous phase and the low-crystalline phase, accelerating electronic communication, thereby improving the inherent catalytic activity; 3) The 3D nanosphere structure provides abundant active sites, shortens the electron / mass transfer path, and significantly accelerates the reaction kinetics.
[0026] The present invention emphasizes the construction of amorphous / low crystalline heterostructures to improve the electrolytic water splitting performance, corrosion resistance and stability of high entropy oxysulfides, and broadens the options for designing low-cost, high-performance bifunctional electrocatalysts. The preparation process provided by the present invention is simple, does not require complex equipment and experimental steps, and is convenient for large-scale preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The X-ray diffraction patterns of the electrocatalysts prepared in Examples 1 to 3 are shown.
[0028] Figure 2 The scanning electron microscope images of the NiCoFeOS / CeO2 electrocatalyst prepared in Example 1, wherein (a) to (d) are scanning electron microscope images at different magnifications.
[0029] Figure 3 The scanning electron microscope images of the NiCoFeOS electrocatalyst prepared in Example 2, wherein (a) to (d) are scanning electron microscope images at different magnifications.
[0030] Figure 4The scanning electron microscope images of the CeO2 electrocatalyst prepared in Example 3, wherein (a) to (d) are scanning electron microscope images at different magnifications.
[0031] Figure 5 This is the EDS element mapping image of the NiCoFeOS / CeO2 electrocatalyst prepared in Example 1.
[0032] Figure 6 High-resolution transmission electron microscope images and electron diffraction images of the NiCoFeOS / CeO2 electrocatalyst prepared in Example 1, wherein (a), (b), and (d) are transmission electron microscope images of different resolutions, and (c) is an electron diffraction image.
[0033] Figure 7 LSV curves of the electrocatalysts and NF substrates prepared in Examples 1 to 3 measured in 1 M KOH with a test voltage range of -0.9 to -1.6 V vs. Hg / HgO.
[0034] Figure 8 LSV curves of the electrocatalysts and NF substrates prepared in Examples 1 to 3 measured in 1 M KOH with a test voltage range of 0.075 to 0.875 V vs. Hg / HgO.
[0035] Fig. 9 LSV curves of the electrocatalysts prepared in Examples 1, 4 and 5 measured in 1 M KOH at a test voltage range of -0.9 to -1.6 V vs. Hg / HgO.
[0036] Fig.10 LSV curves of the electrocatalysts prepared in Examples 1, 4 and 5 measured in 1 M KOH at a test voltage range of 0.075 to 0.875 V vs. Hg / HgO.
[0037] Fig.11 The stability test results of hydrogen evolution in water electrolysis of the NiCoFeOS / CeO2 electrocatalyst prepared in Example 1.
[0038] Fig.12 The stability test results of water electrolysis and oxygen evolution of the NiCoFeOS / CeO2 electrocatalyst prepared in Example 1.
[0039] Fig.13 The results of the full water splitting stability test of the two-electrode system NiCoFeOS / CeO2(+,-) composed of the NiCoFeOS / CeO2 electrocatalyst prepared in Example 1 (a) and the LSV curves of the NiCoFeOS / CeO2 electrocatalyst before and after the full water splitting stability test (b). DETAILED DESCRIPTION
[0040] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0041] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0042] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0043] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0044] Example 1
[0045] Preparation of high entropy amorphous NiCoFeOS and low crystalline CeO2 heterojunction electrocatalysts:
[0046] (1) Pretreatment of nickel foam: The pretreated nickel foam (thickness 1.0 mm) was cut into 1×2 cm 2 , and then ultrasonically cleaned for 20 min in the order of acetone, deionized water, hydrochloric acid and alcohol, and the cleaned nickel foam was dried at 60 °C for 6 h;
[0047] (2) Preparation of electrodeposition solution: Dissolve 12.5 mM NiSO4·6H2O; 12.5 mM CoSO4·7H2O; 12.5 mM FeSO4·7H2O; 12.5 mM Ce(NO3)3·6H2O; 150 mM CH4N2S and 25 mM (NH4)2SO4 in 100 mL of water, mix them evenly under the action of ultrasound to obtain an electrodeposition solution.
[0048] (3) Electrodeposition: Pretreated nickel foam (NF) was used as the working electrode, carbon rod as the counter electrode, and Ag / AgCl as the reference electrode. The prepared electroplating solution was placed in an electrolytic cell with a built-in rotor. The electrolytic cell was maintained at 300 rpm by a magnetic stirrer and the temperature was kept at room temperature. The electrochemical workstation was operated in an intermittent electroplating mode with a controlled voltage. The deposition voltage was -1.8 V vs. Ag / AgCl. The electrochemical workstation was turned off under the static voltage state. Each potential was maintained for 10 s, the cycle was 120 times, and the total deposition time was maintained at 2400 s. The prepared samples were rinsed with deionized water and ethanol, respectively, and dried at 60 °C for 6 h to obtain a high entropy amorphous NiCoFeOS and low crystalline CeO2 heterojunction (NiCoFeOS / CeO2) electrocatalyst.
[0049] Example 2
[0050] Preparation of high entropy amorphous NiCoFeOS electrocatalyst:
[0051] (1) Pretreatment of nickel foam: The pretreated nickel foam (thickness 1.0 mm) was cut into 1×2 cm 2 , and then ultrasonically cleaned for 20 min in the order of acetone, deionized water, hydrochloric acid and alcohol, and the cleaned nickel foam was dried at 60 °C for 6 h;
[0052] (2) Preparation of electrodeposition solution: Dissolve 12.5 mM NiSO4·6H2O; 12.5 mM CoSO4·7H2O; 12.5 mM FeSO4·7H2O; 12.5 mM 150 mM CH4N2S and 25 mM (NH4)2SO4 in 100 mL of water, mix them evenly under the action of ultrasound to obtain an electrodeposition solution.
[0053] (3) Electrodeposition: The pretreated nickel foam was used as the working electrode, the carbon rod was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The prepared electroplating solution was placed in an electrolytic cell with a built-in rotor. The electrolytic cell was maintained at 300 rpm by a magnetic stirrer and the temperature was maintained at room temperature. The electrochemical workstation was operated in an intermittent electroplating mode with a controlled voltage. The deposition voltage was -1.8 V vs. Ag / AgCl. The electrochemical workstation was closed under the static voltage state. Each potential was maintained for 10 s, the cycle was 120 times, and the total deposition time was maintained at 2400 s. The prepared samples were rinsed with deionized water and ethanol, respectively, and dried at 60 °C for 6 h to obtain a high entropy amorphous NiCoFeOS (NiCoFeOS) electrocatalyst.
[0054] Example 3
[0055] Preparation of low-crystalline CeO2 electrocatalyst:
[0056] (1) Pretreatment of nickel foam: The pretreated nickel foam (thickness 1.0 mm) was cut into 1×2 cm 2 , and then ultrasonically cleaned for 20 min in the order of acetone, deionized water, hydrochloric acid and alcohol, and the cleaned nickel foam was dried at 60 °C for 6 h;
[0057] (2) Preparation of electrodeposition solution: 12.5 mM Ce(NO3)3·6H2O and 25 mM (NH4)2SO4 were dissolved in 100 mL of water and mixed uniformly under the action of ultrasound to obtain an electrodeposition solution.
[0058] (3) Electrodeposition: Pretreated nickel foam was used as the working electrode, carbon rod as the counter electrode, and Ag / AgCl as the reference electrode. The prepared electroplating solution was placed in an electrolytic cell with a built-in rotor. The electrolytic cell was maintained at 300 rpm by a magnetic stirrer and the temperature was kept at room temperature. The electrochemical workstation was operated in an intermittent electroplating mode with a controlled voltage. The deposition voltage was -1.8V vs. Ag / AgCl. The electrochemical workstation was closed under the static voltage state. Each potential was maintained for 10s, the cycle was 120 times, and the total deposition time was maintained at 2400s. The prepared samples were rinsed with deionized water and ethanol, respectively, and dried at 60°C for 6h to obtain a low-crystalline CeO2 (CeO2) electrocatalyst.
[0059] The element contents of the electrocatalysts prepared in Examples 1 to 3 are shown in Table 1.
[0060] Table 1
[0061]
[0062] The X-ray diffraction patterns of the electrocatalysts prepared in Examples 1 to 3 are shown in Figure 1 .
[0063] from Figure 1 It can be seen that the CeO2 electrocatalyst exhibits characteristic peaks of low crystallinity, which can be well matched with the characteristic peaks of ceria; the NiCoFeOS electrocatalyst spectrum shows an amorphous structure; the results of the NiCoFeOS / CeO2 electrocatalyst show some characteristic peaks of low crystallinity, corresponding to the peaks of the (111)(220) crystal plane of ceria. The presence of high entropy effectively regulates the d-band center and promotes the reaction kinetics. Amorphous transition metal oxysulfide-based electrocatalysts with more active sites show higher activity than crystalline catalysts. At the same time, due to the good electronic communication between different components, the formation of heterogeneous structures can improve the intrinsic activity of the catalyst.
[0064] The scanning electron microscope image of the NiCoFeOS / CeO2 electrocatalyst prepared in Example 1 is shown in Figure 2 , where (a) to (d) are scanning electron microscope images at different magnifications.
[0065] Figure 2 It is shown that the morphology of NiCoFeOS / CeO2 electrocatalyst is nanospheres covered with wrinkled nanosheets on the NF substrate and nanospheres, which will lead to more exposed active sites and faster material transport efficiency.
[0066] The scanning electron microscopy image of the NiCoFeOS electrocatalyst prepared in Example 2 is shown in Figure 3 , where (a) to (d) are scanning electron microscope images at different magnifications.
[0067] Figure 3 It shows that the NiCoFeOS electrocatalyst is also in the form of nanospheres, which are relatively small in size and relatively smooth, resulting in a relatively small specific surface area and low intrinsic activity.
[0068] The scanning electron microscope image of the CeO2 electrocatalyst prepared in Example 3 is shown in Figure 4 , where (a) to (d) are scanning electron microscope images at different magnifications.
[0069] Figure 4 It is shown that the morphology of CeO2 electrocatalyst is extremely smooth nanospheres with small size, which also leads to its low intrinsic activity.
[0070] The EDS element mapping image of the NiCoFeOS / CeO2 electrocatalyst prepared in Example 1 is shown in Figure 5 .
[0071] from Figure 5 It can be seen that the elements Ni, Co, Fe, Ce, O and S can be evenly present on the surface of the electrocatalyst, proving the success of the catalyst preparation by electrodeposition.
[0072] The high-resolution transmission electron microscope image and electron diffraction image of the NiCoFeOS / CeO2 electrocatalyst prepared in Example 1 are shown in Figure 6 , where (a), (b), and (d) are transmission electron microscope images of different resolutions, and (c) is an electron diffraction image.
[0073] from Figure 6 In (a) and (b), it can be seen that the morphology of the nanospheres is similar to the SEM images; Figure 6 (c) shows two obvious diffraction rings, which correspond to the (111)(220) crystal planes of ceria, which is consistent with the XRD results. Figure 6Amorphous structures and low-crystalline lattice fringes can be observed in (d), which demonstrates the successful preparation of the as-prepared electrocatalyst heterostructure.
[0074] Example 4
[0075] Preparation of high entropy amorphous NiCoFeOS and low crystalline CeO2 heterojunction electrocatalysts:
[0076] Compared with Example 1, the only difference is that the deposition voltage in the intermittent electrodeposition mode is -1.8V vs. Ag / AgCl, the electrical workstation is in the off state in the static voltage state, each potential is maintained for 20s, the cycle period is 60 turns, and the total deposition time is maintained at 2400s.
[0077] Example 5
[0078] Preparation of high entropy amorphous NiCoFeOS and low crystalline CeO2 heterojunction electrocatalysts:
[0079] Compared with Example 1, the only difference is that the intermittent electrodeposition mode is replaced by the pulse electrodeposition mode, the deposition voltage of the pulse electrodeposition is -1.8V and -0.85V vs.Ag / AgCl, each potential is maintained for 20s, the cycle period is 60 turns, and the total deposition time is maintained at 2400s.
[0080] Electrochemical performance test: The three-electrode system was used to test the linear sweep voltammetry in 1M KOH solution to obtain the LSV curve and the chronopotentiometry curve. When the three electrodes were working, the working electrode was the prepared catalyst, the reference electrode was the Hg / HgO electrode, and the counter electrode was the platinum sheet and the carbon rod. The scanning rate of the linear sweep cyclic voltammetry curve was 2mV / s; the potential in the polarization curve was converted from the Hg / HgO electrode to the standard hydrogen electrode E RHE , the conversion relationship is: E RHE =(E Hg / HgO +0.098+0.059pH)V, test solution pH=14.
[0081] The LSV curves of the electrocatalysts and NF substrates prepared in Examples 1 to 3 were measured in 1M KOH with a test voltage range of -0.9 to -1.6 V vs. Hg / HgO. Figure 7 .
[0082] pass Figure 7 It can be clearly observed that the NiCoFeOS / CeO2 electrocatalyst has the best hydrogen evolution performance, indicating that the construction of a heterogeneous structure is beneficial to the improvement of the intrinsic activity of the catalyst for hydrogen evolution.
[0083] The LSV curves of the electrocatalysts and NF substrates prepared in Examples 1 to 3 were measured in 1M KOH with a test voltage range of 0.075 to 0.875 V vs. Hg / HgO. Figure 8 .
[0084] pass Figure 8 It can be clearly observed that the NiCoFeOS / CeO2 electrocatalyst has the best oxygen evolution performance, indicating that after constructing a heterogeneous structure, it is also beneficial to improve the intrinsic activity of the catalyst for oxygen evolution.
[0085] The LSV curves of the electrocatalysts prepared in Examples 1, 4 and 5 were measured in 1M KOH with a test voltage range of -0.9 to -1.6 V vs. Hg / HgO. Fig. 9 .
[0086] Fig. 9 It shows that the NiCoFeOS / CeO2 electrocatalyst prepared under the electrodeposition conditions of Example 1 has the best hydrogen evolution catalytic performance.
[0087] The LSV curves of the electrocatalysts prepared in Examples 1, 4 and 5 were measured in 1M KOH with a test voltage range of 0.075 to 0.875 V vs. Hg / HgO. Fig.10 .
[0088] Fig.10 It shows that the NiCoFeOS / CeO2 electrocatalyst prepared under the electrodeposition conditions of Example 1 has the best oxygen evolution catalytic performance.
[0089] The NiCoFeOS / CeO2 electrocatalyst prepared in Example 1 was tested for stability of hydrogen evolution by electrolysis of water. Fig.11 .
[0090] Fig.11 Display, at 50mA·cm -2 At a current density of , a chronopotentiometry test was carried out for up to 100 h, and the test potential had almost no obvious decrease, indicating that the NiCoFeOS / CeO2 catalyst prepared in Example 1 has excellent HER durability.
[0091] The NiCoFeOS / CeO2 electrocatalyst prepared in Example 1 was tested for stability of oxygen evolution in water electrolysis. Fig.12 .
[0092] Fig.12 Display, at 50mA·cm -2At a current density of , a chronopotentiometry test was carried out for up to 100 h, and the test potential had almost no obvious increase, indicating that the NiCoFeOS / CeO2 catalyst prepared in Example 1 has excellent OER durability.
[0093] The NiCoFeOS / CeO2 electrocatalyst prepared in Example 1 was used to form a two-electrode system NiCoFeOS / CeO2 (+, -) for the overall water splitting stability test. The LSV curves of the NiCoFeOS / CeO2 electrocatalyst before and after the overall water splitting stability test were compared. The test results are shown in FIG. Fig.13 , where (a) is the result of the overall water splitting stability test, and (b) is the LSV curve of the NiCoFeOS / CeO2 electrocatalyst before and after the overall water splitting stability test.
[0094] Fig.13 (a) shows that the NiCoFeOS / CeO2(+, -) full water splitting performance has almost no attenuation, showing good long-term stability of water electrolysis; Fig.13 (b) shows that the LSV curves before and after the full water splitting stability test are almost completely overlapped, and the assembled two-electrode device can reach 10 mA cm at only 1.54 V. -2 of current density.
[0095] The above experimental results show that the present invention uses a one-step intermittent electrodeposition method to prepare a high-entropy amorphous NiCoFeOS and low-crystalline CeO2 heterojunction electrocatalyst uniformly loaded on nickel foam, and the performance of NiCoFeOS / CeO2, NiCoFeOS, and CeO2 electrocatalysts is characterized. The results show that the NiCoFeOS / CeO2 electrocatalyst has the best electrolysis performance of water, confirming that the formation of heterostructures helps to improve the intrinsic activity of the catalyst, optimize the binding energy of intermediates, and enhance the electron transfer rate. The high-entropy amorphous-low-crystalline heterostructure has rich defects and high active sites, thereby improving the intrinsic catalytic activity. The enhanced charge transfer at the active interface between the amorphous phase and the low crystalline phase accelerates electronic communication. The electrocatalyst with a 3D nanosphere structure provides abundant active sites, shortens the electron / mass transfer path, and significantly accelerates the reaction kinetics. Changes in electrodeposition parameters and electrodeposition methods have an impact on the performance of the prepared high-entropy amorphous NiCoFeOS and low-crystalline CeO2 heterojunction electrocatalysts.
[0096] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a high entropy amorphous NiCoFeOS and low crystalline CeO2 heterojunction electrocatalyst, characterized in that: The following steps are involved: Dissolving a soluble nickel salt, a soluble cobalt salt, a soluble iron salt, a soluble cerium salt, thiourea and ammonium sulfate in water to prepare an electrodeposition solution; The electrodeposition liquid is used to form an electrodeposition layer on a substrate through electrodeposition, and the electrodeposition layer is the high-entropy amorphous NiCoFeOS and low-crystalline CeO2 heterojunction electrocatalyst.
2. The method for preparing the high entropy amorphous NiCoFeOS and low crystalline CeO2 heterojunction electrocatalyst according to claim 1, characterized in that: The molar ratio of nickel in the soluble nickel salt, cobalt in the soluble cobalt salt, iron in the soluble iron salt and cerium in the soluble cerium salt is 0.9-1.1:0.9-1.1:0.9-1.1:0.9-1.
1.
3. The method for preparing the high entropy amorphous NiCoFeOS and low crystalline CeO2 heterojunction electrocatalyst according to claim 1, characterized in that: The molar ratio of the total amount of metal sources in the soluble nickel salt, the soluble cobalt salt, the soluble iron salt and the soluble cerium salt to the thiourea is 1:2.8-3.
2.
4. The method for preparing the high entropy amorphous NiCoFeOS and low crystalline CeO2 heterojunction electrocatalyst according to claim 1, characterized in that: The soluble nickel salt is nickel sulfate; the soluble cobalt salt is cobalt sulfate; the soluble iron salt is ferrous sulfate; and the soluble cerium salt is cerium nitrate.
5. The method for preparing a high entropy amorphous NiCoFeOS and low crystalline CeO2 heterojunction electrocatalyst according to claim 1, characterized in that: The electrodeposition is intermittent electrodeposition.
6. The method for preparing the high entropy amorphous NiCoFeOS and low crystalline CeO2 heterojunction electrocatalyst according to claim 5, characterized in that: The deposition voltage of the intermittent electrodeposition is -1.8 V, the static voltage is 0, each voltage holding time is 10 s, and the total intermittent electrodeposition time is 2400 s.
7. The method for preparing a high entropy amorphous NiCoFeOS and low crystalline CeO2 heterojunction electrocatalyst according to claim 1, characterized in that: The substrate is nickel foam; in the electrodeposition, the working electrode is nickel foam, the counter electrode is a carbon rod, and the reference electrode is Ag / AgCl.
8. A high entropy amorphous NiCoFeOS and low crystalline CeO2 heterojunction electrocatalyst prepared according to the preparation method according to any one of claims 1 to 8.
9. Use of the high entropy amorphous NiCoFeOS and low crystalline CeO2 heterojunction electrocatalyst as described in claim 8 in water electrolysis.